Evaluation of a novel virtual reality training intervention to address implicit bias among healthcare workers, using an implementation science framework - Olmos-Rodriguez, Madelyn; Anicete, Lynhea M.; Wilson, Nova; Gutierrez-Mock, Luis; Bailenson, Jeremy N.; Mirzazadeh, Ali; Harris, Orlando O.; Dandu, Madhavi; Welty, Suzanne; Fernandez, Alicia; Rojo, Elizabeth M.; Harris, Savanna; et al. (PloS one, 2025)
There is a link between racial bias and poor health outcomes among Black, Indigenous, and People of Color (BIPOC). We aimed to design and evaluate a novel pilot virtual reality (VR) training program to reduce racial bias among healthcare providers in a university healthcare system. CULTIVATE (Combatting Unequal Treatment in Healthcare Through Virtual Awareness in Empathy) is a mixed-methods study utilizing virtual reality (VR) training to enhance healthcare providers' empathy towards racially and linguistically discordant patients. Participants included White-identifying clinical providers and graduate-level healthcare students, excluding those not engaged in direct patient care, BIPOC providers, and individuals unable to participate in VR training. Empathy was measured using a situational empathy scale and the Jefferson Empathy Scale (JSE) before and after the intervention, which comprised two VR modules, empathy assessments, and a qualitative interview. Quantitative and qualitative analyses were performed using the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework to evaluate the program. The RE-AIM model will structure a framework for understanding virtual reality's utility in future healthcare practice. Reach: 30 adults participated, mostly women (n = 21), 47% were physicians, and 8% had no prior implicit bias training. Eighteen participants completed pre- and post-VR empathy assessments and interviews. Effectiveness: There was no significant difference in mean JSE scores pre- (120.7) and post-intervention (122.2), but qualitative data indicated increased emotional responses. Adoption: Participants endorsed the intervention with a mean score of 8 (SD = 2) on a 10-point Likert scale for recommending it to others. Implementation: The program followed the pre-designed protocol. Maintenance: Participants reported improved clinical empathy towards BIPOC patients in qualitative analyses. In this pilot study, participants found VR training to be acceptable and feasible. A larger sample needs to participate in the intervention to determine effectiveness. Qualitative results demonstrated that VR training enhanced empathy.